2014
DOI: 10.1053/j.gastro.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Activation of EGFR and ERBB2 by Helicobacter pylori Results in Survival of Gastric Epithelial Cells With DNA Damage

Abstract: BACKGROUND & AIMS The gastric cancer-causing pathogen Helicobacter pylori upregulates spermine oxidase (SMOX) in gastric epithelial cells, causing oxidative stress-induced apoptosis and DNA damage. A subpopulation of SMOXhigh cells are resistant to apoptosis, despite their high levels of DNA damage. Because epidermal growth factor receptor (EGFR) activation can regulate apoptosis, we determined its role in SMOX-mediated effects. METHODS SMOX, apoptosis, and DNA damage were measured in gastric epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 44 publications
(49 reference statements)
5
90
0
Order By: Relevance
“…24,25 Infection also increases the level of spermine oxidase (SMOX), which catabolizes spermine and produces hydrogen peroxide (H 2 O 2 ) and leads to DNA damage in gastric epithelial cells, a key event in the process of gastric carcinogenesis. 2629 In the present study we demonstrate that H. pylori strains from the high risk region of Nariño, Colombia induce more SMOX and associated DNA damage in vitro and in vivo . We used inhibitors of ODC and SMOX and found that polyamine synthesis and oxidation drive H. pylori -associated gastric carcinogenesis in a gerbil model of gastric cancer.…”
Section: Introductionsupporting
confidence: 54%
“…24,25 Infection also increases the level of spermine oxidase (SMOX), which catabolizes spermine and produces hydrogen peroxide (H 2 O 2 ) and leads to DNA damage in gastric epithelial cells, a key event in the process of gastric carcinogenesis. 2629 In the present study we demonstrate that H. pylori strains from the high risk region of Nariño, Colombia induce more SMOX and associated DNA damage in vitro and in vivo . We used inhibitors of ODC and SMOX and found that polyamine synthesis and oxidation drive H. pylori -associated gastric carcinogenesis in a gerbil model of gastric cancer.…”
Section: Introductionsupporting
confidence: 54%
“…H. pylori upregulates the expression of EGF-related growth factors, which activate EGFR and other tyrosine kinase receptors, and then stimulate proliferation and survival through PI3K-AKT and mitogen-activated protein kinases (MAPK) pathways. 46 Notably, we have previously shown that DARPP-32 plays an important role in stabilisation of EGFR and activation of AKT in gastric cancer cells. 6 Taken together, the fact that DARPP-32 expression is induced by H. pylori-activated NF-κB strongly suggests that DARPP-32 oncogenic functions may contribute to H. pylori-mediated gastric tumourigenesis.…”
Section: H Pylori Activates the Prosurvival Akt Pathway Through Regumentioning
confidence: 99%
“…Small intestines were harvested 4 h postirradiation and ϳ3-to 4-cm segments of the distal small intestine were excised and further dissected before snap freezing in liquid nitrogen for use in subsequent flow cytometric analysis (8,9). The remaining section of the distal small intestine was Swissrolled, fixed, and submitted to the Vanderbilt TPSR core for processing and sectioning.…”
Section: Immunohistochemistry and Immunofluorescencementioning
confidence: 99%